Propuesta de un plan estratégico para la empresa megaclima cía. LTDA de la ciudad de Loja, para el periodo 2013 –2018 - Maldonado Daniela, Daniela Paute (2014)
This thesis is entitled: "Proposal for a Strategic Plan for the company MEGACLIMA Co.. Ltda Loja, for the period 2013 - 2018 "In an effort to streamline all internal processes of the organization was undertaken in conducting this investigation, which has as its main objective:" Develop a Strategic Plan for Company "MEGACLIMA CIA. LTDA "City of Loja, Loja Province, Period 2013 - 2018". The methodology used for the elaboration of the research was revistada by the use of the following methods: Historical, Deductive, Inductive, Analytical, statistical and descriptive; also resorted to the use of the following techniques: The Observation, Interview and Survey. In the process of development of different research aspects addressed during the development of the investigation, it had to comply consistently with the following essential technical and methodological approach for the development of strategic plans: In order to have clear knowledge about the current situation being experienced by the company MEGACLIMA Co.. Ltd. In various aspects such as:. Administrative organization, departmental distribution, material resources, technological resources, human resources, etc, in the first instance was used to conduct a situational analysis of the company MEGACLIMA Co.. Ltd.